O processo saúde-doença dos/as trabalhadores/as da sericicultura no Paraná - Pinto, Nanci Ferreira (2015)
Sericulture, the rearing of silkworm for the production of silk cocoons, is an activity included in the agro-industrial complex of silk, monopolized by one company in Brazil. It is executed by small farmers and their families. International studies indicate the occurrence of diseases related to this activity. In Brazil, there are no studies on these workers health. This research aimed at understanding the health-disease process of sericulture workers in the State of Paraná. Qualitative analysis was carried out through observations, interviews and focus group. Nine sericulture workers were interviewed in the cities of Arapongas and Diamante do Sul, in Paraná. The focus group was conducted with four interviewees in the city of Arapongas. Data examining was based on the identification of the elements that corresponded to the singular, the particular and the general instances, taking as a guide the work process category, which produced the interrelation with the health-disease process. The families way of life is characterized by difficulty in developing autonomous production lines, difficult access to public credit, lack of public technical assistance to other production lines, seasonal income, and development of various activities in order to arrange their income. In the technical process of work, there is the contact with toxic chemical substances, prolonged working hours, situations of suffering, and risk of accident with fire and snakes. Complaints and injuries were reported: physical fatigue, backache, chronic laryngitis, shortness of breath, gastritis, eye irritation, stomachache, stress, and anxiety. Monitoring the health of sericulture workers and their families is urgent. There is a lack of information for the workers about loads, work processes and health effects. It is up to the Brazilian unified health system SUS to develop strategies for communicating risk. There is need for studies about child and adolescent labor in the integrated production system. Situations related to accidents with snakes and fire must be monitored